THE EFFECT OF POLITICAL CONNECTIONS, PROFITABILITY, AND LEVERAGE ON TAX AVOIDANCE - Nabilah Fathiyah Rachma; Janiman Lie (IJEBD (International Journal of Entrepreneurship and Business Development), 2026)
Purpose: The purpose of this study is to analyze the influence of political connections, profitability, and leverage on tax avoidance. This study was conducted on infrastructure and utility companies listed on the Indonesia Stock Exchange (IDX) from 2022 to 2024. Design/methodology/approach: This study uses a quantitative method with multiple linear regression analysis tools. The sampling method uses purposive sampling with a sample size of 117 during 2022-2024. Result: summarize the result or findings of your study. Findings: Political connections and leverage variables influence tax avoidance, while profitability variables do not influence tax avoidance. Research limitations/implications: In this study, the adjusted R square value was only 13%, which means that the independent variables did not explain much of the dependent variable, and the contribution of political connections, profitability, and leverage to tax avoidance was only 13%, while the remaining 87% was contributed by other factors not examined in this study. Practical implications: This study is expected to contribute to the development of knowledge in the fields of accounting and taxation by improving understanding of the influence of political connections, profitability, and leverage on tax avoidance practices. In practical terms, this research can be taken into consideration by companies in determining their taxation strategies, by investors in making investment decisions, and by students as a reference regarding factors that influence tax avoidance. In addition, in terms of policy, this research can be used as material for evaluation and consideration in designing effective taxation strategies that comply with regulations and minimize companies' reputational and legal compliance risks. Paper type: Research paper Keyword: tax avoidance; political connections; profitability; leverage